2021
DOI: 10.5888/pcd18.210193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Municipal-Level Policies Dedicated to Transportation That Consider Food Access

Abstract: Introduction Local governments can address access to healthy food and transportation through policy and planning. This study is the first to examine municipal-level transportation supports for food access. Methods We used a nationally representative sample of US municipalities with 1,000 or more persons from the 2014 National Survey of Community-Based Policy and Environmental Supports for Healthy Eating and Active Living (N = 2,029) to assess 3 outcomes: public transit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since previous studies have reported individuals living in rural and poor areas have limited access to food due to transportation (56) , legislation can be used to improve transportation to help close the gap in food security. For example, an affordable and publicly run Grocery Bus line that was assimilated into the regular transit system in Austin, Texas intentionally connected a low-income Latinx community with insufficient transportation limiting supermarket access (56) . Finally, policies mitigating climate change may also help improve food security status (47) .…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have reported individuals living in rural and poor areas have limited access to food due to transportation (56) , legislation can be used to improve transportation to help close the gap in food security. For example, an affordable and publicly run Grocery Bus line that was assimilated into the regular transit system in Austin, Texas intentionally connected a low-income Latinx community with insufficient transportation limiting supermarket access (56) . Finally, policies mitigating climate change may also help improve food security status (47) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, municipal and regional transportation policies that improve multimodal access to healthy food are needed to improve access for individuals and families who have limited access to a private automobile (Swayne and Lowery 2021). Some examples of this might include explicit consideration of food access when determining public transit routes and schedules, and the provision of community vans or shuttle buses to link residents directly to food outlets (Dumas et al 2021). Previous survey work among U.S. municipalities has found that less than 15% of cities offer community vans and/ or shuttle buses, and less than 40% of cities with public transit considered food access when route planning (Dumas et al 2021).…”
Section: Societal Transformationmentioning
confidence: 99%
“…Some examples of this might include explicit consideration of food access when determining public transit routes and schedules, and the provision of community vans or shuttle buses to link residents directly to food outlets (Dumas et al 2021). Previous survey work among U.S. municipalities has found that less than 15% of cities offer community vans and/ or shuttle buses, and less than 40% of cities with public transit considered food access when route planning (Dumas et al 2021). While these results suggest scant attention to food access in the context of transportation planning and provision, these approaches can and should be implemented by local government and transportation officials to support access to healthy food (Dumas et al 2021).…”
Section: Societal Transformationmentioning
confidence: 99%
See 1 more Smart Citation